Managing incidental pancreatic cystic neoplasms with integrated molecular pathology is a cost-effective strategy - Das, Ananya; Brugge, William; Mishra, Girish; Smith, Dennis M.; Sachdev, Mankanwal; Ellsworth, Eric (Endoscopy International Open, 2015)
Background and study aims: Current guidelines recommend using endoscopic ultrasound (EUS), carcinoembryonic antigen (CEA) testing and cytology to manage incidental pancreatic cystic neoplasms (PCN); however, studies suggest a strategy including integrated molecular pathology (IMP) of cyst fluid may further aid in predicting risk of malignancy. Here, we evaluate several strategies for diagnosing and managing asymptomatic PCN using healthcare economic modeling.Patients and methods: A third-party-payer perspective Markov decision model examined four management strategies in a hypothetical cohort of 1000 asymptomatic patients incidentally found to have a 3 cm solitary pancreatic cystic lesion. Strategy I used cross-sectional imaging, recommended surgery only if symptoms or risk factors emerged. Strategy II considered patients for resection without initial EUS. Strategy III (EUS + CEA + Cytology) referred only those with mucinous cysts (CEA > 192 ng/mL) for resection. Strategy IV implemented IMP; a commercially available panel provided a “Benign,” “Mucinous,” or “Aggressive” classification based on the level of mutational change in cyst fluid. “Benign” and “Mucinous” patients were followed with surveillance; “Aggressive” patients were referred for resection. Quality-adjusted life-years (QALY), relative risk with 95 %CI, Number Needed to Treat (NNT), and incremental cost-effectiveness ratios were calculated.Results: Strategy IV provided the greatest increase in QALY at nearly identical cost to the cheapest approach, Strategy I. Relative risk of malignancy compared to the current standard of care and nearest competing strategy, Strategy III, was 0.18 (95 %CI 0.06 – 0.53) with an NNT of 56 (95 %CI 34 – 120).Conclusions: Use of IMP was the most cost-effective strategy, supporting its routine clinical use.